Exploring the Mode of Entrepreneurship Education Based on the Legal-Business Compound Competency in China - Wang, Ting (Frontiers in Psychology, 2019)
A perfect legal guarantee can ensure China’s high-quality socio-economic development. At present, in terms of China’s entrepreneurship education (EE), it is necessary to strengthen entrepreneurs’ legal consciousness and respect for rules. The research establishes a model for legal-business compound competency (LBCC). It is a pioneering EE mode adapted to characteristics of China’s market transition to cultivate interdisciplinary talents who excel at management and administration but also have a command of laws and regulations in EE. By utilising behavioural event interview (BEI) and Delphi methods, factors affecting LBCC were summarised. Moreover, a questionnaire-based inquiry was conducted using graduates who received law–business interdisciplinary entrepreneurship education (LBIEE) as subjects to collecting data to evaluate the cultivation effect of the EE mode. In the study, a model for LBCC was established from the three perspectives including knowledge, skill, and attitude. Additionally, cultivating competency of law–business interdisciplinary talents (LBITs) shows a significantly positive influence on compensation level and job satisfaction among graduates who have received the EE. The core task of LBIEE is to improve compound competency of students in legal-business to enable students to show entrepreneurial spirit with legal-business intelligence. It is considered an innovation in a mode of education adapted to the transition and development of China’s market economy.